2006
DOI: 10.1016/j.ejcts.2006.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal ischaemia following cardiac surgery: a multivariate risk model☆

Abstract: Although the incidence of intestinal ischaemia following cardiac surgery is low, the prognosis for these patients is very poor. We have identified several risk factors, and developed a multivariate prediction tool, which may be useful in identifying patients at high-risk of developing intestinal ischaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 21 publications
3
25
1
4
Order By: Relevance
“…We found a lower incidence, 0.09%, than previously presented, but the mortality rate was comparable with others [4,10,12,18-20]. Risk factors were identified that can aid in the diagnosis.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We found a lower incidence, 0.09%, than previously presented, but the mortality rate was comparable with others [4,10,12,18-20]. Risk factors were identified that can aid in the diagnosis.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, when investigating preoperative factors we found the use of steroids, peripheral vascular disease, cardiogenic chock, and NYHA class 4 to be independent prognostic factors for development of the complication. Peripheral vascular disease has previously been pointed out as a risk factor as well as a poor preoperative cardiac condition [5,10,12]. In one older publication, the use of steroids - but in that case postoperatively - was a factor associated with an increased risk of general surgical complications after cardiac surgery [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of preoperative A Fib on gastrointestinal complications is a direct result of both low output state and embolic nature of such cases. These can lead to bowel ischemic or unstable gastrointestinal haemorrhages from low perfusion state [9]. Data on short-term mortality in A Fib patients are rather conflicting (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the heart, the intestine is also commonly affected by I/R injury, which can be due to, for example, cardiac arrest (6), hemorrhagic shock (7), burn trauma (8) or vascular and cardiac surgery (9)(10)(11). Animal studies and clinical observations revealed that ischemia leads to increased permeability of the intestinal epithelial barrier, resulting in translocation of pathogenic bacteria and endotox- ins (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%